Influence mechanism of defects in aluminum alloy friction stir welding on fatigue life (Fracture and Structural Integrity, 2026)
By controlling welding parameters and adjusting process conditions, three typical defects-oxide inclusions, tunnel defects, and lack-of-penetration defects-were intentionally introduced during the friction stir welding (FSW) of aluminum alloys. A comparative analysis of fatigue S-N curves between sound joints and joints with the three types of defects was conducted to systematically evaluate the impact of different defect types on the fatigue performance of welded joints. The results demonstrated that all three defects significantly reduce the fatigue life of the joints, with lack-of-penetration defects having the most pronounced effect, followed by tunnel defects and oxide inclusions. Fracture surface analysis using SEM, EDS, and Microhardness testing confirmed that defects act as the primary crack initiation sites—the sound joint initiated cracks at the arc-textured surface, whereas cracks in all defective joints originated from the defect regions. Building on these fractographic findings, the intrinsic micro-mechanism responsible for the systematic decrease in the S-N curve slope —from 7.14 for the sound joint to 2.74 for the LOP defect joint—was elucidated: the geometric sharpness and interfacial bonding state of a defect compress the crack initiation stage, shifting the dominant failure mode from initiation-dominated to propagation-dominated, which in turn manifests as a reduction in m.
Keywords: Friction Stir Welding (FSW); Oxide Inclusion Defects; Tunnel Defects; Lack of Penetration Defects